Improving Mathematics Learning Results By Implementing Circ Cooperative Learning Model - Kasmidawati Kasmidawati (Jurnal Ilmiah Pendidikan Scholastic, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do it", that is to describe something in their own way, to show their example, to try to practice their skills and to do tasks that demand the knowledge they have gained. The problems to be studied in this research are: Does the implementation of CIRC Cooperative Learningtipe model can improve the learning outcomes of mathematics? Steps taken in this model. Subject peneliatiannya is a fourth grader elementary school, conducted in class IV in addition to researchers teaching this class, because the class has problems according to the studied. Research involving two mathematics teachers in grade IV SDN 07 Pasar Salido. One teacher as the lead researcher and one other teacher as observer. This study was conducted in 3 cycles. Each cycle has 4 stages. Namely (1) Planning, (2) Action, (3) Observation, and (4) Reflection. Data analysis was done by using comparative descriptive analysis that is comparing test value between cycles with work indicator. So the data analysis in this research is done both quantitatively and qualitatively. Test results in the analysis quantitatively based on prosestase. While the data obtained from the observations were analyzed qualitatively. Some conclusions that can be drawn from the results of classroom action research (PTK) is as follows: 1) Student learning motivation in general has increased the average of motivation is quite good at the beginning of 75% of students to 90% of students in grade IV SDN 07 Salido Market. This is according to the analysis of the researcher as follows: (1) Students are happy with the variation of the learning model that they think new and they have never been before (2) The learning material discussed is relatively understandable by the students because in the previous school level has been taught. The results of tests performed on each cycle increased, except in cycle III. In cycle I the average value of 65.40, in cycle II the average value of 69.00 and in cycle III the average value of 68.00. This is according to the observation and experience of researchers because for the material students in cycle III about the media is relatively more difficult than the material in cycles I and II.